2016
DOI: 10.1055/s-0041-111823
|View full text |Cite
|
Sign up to set email alerts
|

Acid Violet 17: a New Dye for Chromovitrectomy?

Abstract: Preclinical tests indicate that AV17 has toxic and undesired effects at concentrations much lower than claimed by suppliers. Against the background of these data and the first observations of adverse clinical effects, it seems advisable to be cautious when using AV17.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 7 publications
(32 reference statements)
0
14
0
Order By: Relevance
“…These were: 1. F6H8 as a heavy endotamponade for the treatment of retinal detachment, leading to chronic hypotonia in the majority of treated cases [15], 2. a toxic perfluoro-octane for intraoperative use leading to acute and severe retinal necrosis [16], and 3. the chromovitrectomy dye acid violet 17 causing severe damage to the RPE in some cases of full thickness macular hole [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These were: 1. F6H8 as a heavy endotamponade for the treatment of retinal detachment, leading to chronic hypotonia in the majority of treated cases [15], 2. a toxic perfluoro-octane for intraoperative use leading to acute and severe retinal necrosis [16], and 3. the chromovitrectomy dye acid violet 17 causing severe damage to the RPE in some cases of full thickness macular hole [2].…”
Section: Discussionmentioning
confidence: 99%
“…Eine kurze Übersicht zur Sicherheit von Bromphenolblau bei farbstoffassistierten vitreoretinalen Interventionen the regular process of product approval few years ago, proved to cause undesired outcomes in cases with full thickness macular holes [2]. A review of biocompatibility data revealed that the approval was granted although biocompatibility data clearly indicated toxic effects to ocular structures at much lower concentrations than marketed [3].…”
Section: A Short Review On the Safety Of Bromphenol Blue For Dye-assimentioning
confidence: 99%
“…incidence of degradation products, drop in pH, may contribute to the explanation of the reported clinical adverse effects in AV-assisted peeling of the internal limiting membrane, in particular in patients with macular holes [7]. Another additional reason might be the concentration of the AV solution which was commercially available until recently.…”
Section: Discussionmentioning
confidence: 99%
“…92 Ala Medics introduced Ala Purple to the market at a concentration of 1.5 mg/ml. Shortly thereafter, several publications suggesting the dye not be used due to the toxicity at commercially available concentrations, [121][122][123] and the company pulled the product from the market. Subsequent in vitro studies further supported the toxicity profile of Acid Violet.…”
Section: Investigational Dyesmentioning
confidence: 99%